Blending a New Polymers Containing Oxadiazole Ring with PVA: Synthesis , Thermal Analysis and Biological Activity - Saeed, Ruwaidah S.; Ghali, Thaer Saleh; Alwitry, Zahraa A.; Tomma, Jumbad H.; Al-rawi, Muna S. (Iraqi Journal of Science, 2025)
This study focused on the synthesis of novel polymers incorporating the 1,3,4-oxadiazole ring. Four polymers were specifically prepared by blending polymers (6-9) with polyvinyl alcohol (PVA) in defined ratios, resulting in the formation of blended polymers (10-13). The synthesized polymers were characterized using Fourier Transform Infrared (FTIR) spectroscopy and proton nuclear magnetic resonance (1H-NMR). The results showed that the structure aligned with the proposed synthetic polymers. Furthermore, the physical and thermal properties were studied using scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC). Additionally, the biological activity was examined against two strains of pathogenic bacteria, Gram-negative (E. Coli) and Gram-positive (S. aureus). The findings demonstrated greater activity than Amoxicillin as a standard antibiotic.